The Perspective of Family Functionality on Juvenile Delinquency Among Female Motorcycle Gangs - Leni Armayati; Resti Anjeli (Journal of Practice Learning and Educational Development, 2025)
Motorcycle gangs are no longer exclusively associated with male dominance; they have increasingly involved females as well. The actions of female motorcycle gangs have become a growing concern due to their involvement in violent behaviors such as assaults, fights, and illegal street racing. Family functionality plays a crucial role in preventing adolescents from engaging in delinquent behavior, especially among members of female motorcycle gangs. This study aims to examine the relationship between family functionality and juvenile delinquency among female motorcycle gang members. The sample consisted of 40 female motorcycle gang members in Pekanbaru, selected using a saturated sampling technique. Data were collected using two scales: the Family Assessment Device, which was adapted into Indonesian by the researcher through a forward translation technique, and the Self-Reported Delinquency Scale, which had previously been adapted into Indonesian. The results show a significant negative correlation between family functionality and juvenile delinquency among female motorcycle gang members (r = -0.487; p = 0.00; p < 0.01). This indicates that higher family functionality is associated with lower levels of juvenile delinquency among female motorcycle gang members. Conversely, lower family functionality is associated with higher levels of delinquency in this group.